1997
DOI: 10.1097/00000539-199711000-00024
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Epidural Saline Injection on Analgesic Level During Combined Spinal and Epidural Anesthesia Assessed Clinically and Myelographically

Abstract: In this study, using surgical patients and volunteers, we determined that a lumbar epidural injection of physiological saline solution 10 min after spinal anesthesia produces a higher analgesic level than spinal anesthesia alone because of a volume effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
65
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 11 publications
7
65
0
2
Order By: Relevance
“…Study demonstrated that the contrast medium in the subarachnoid space was displaced in a cephalad direction after the lumber epidural injection of saline and that the diameter of the subarachonoid space narrowed due to the volume effect. 13 It was suggested that volume effect is time dependent and is seen when epidural top up is done soon after spinal injection. This volume effect is abolished when patients are left seated for 5 minutes after spinal injection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Study demonstrated that the contrast medium in the subarachnoid space was displaced in a cephalad direction after the lumber epidural injection of saline and that the diameter of the subarachonoid space narrowed due to the volume effect. 13 It was suggested that volume effect is time dependent and is seen when epidural top up is done soon after spinal injection. This volume effect is abolished when patients are left seated for 5 minutes after spinal injection.…”
Section: Discussionmentioning
confidence: 99%
“…They thought this is unlikely as other studies had demonstrated the effect with lower dose of EVE only 5 ml and 6 ml EVE. 13,16 To avoid these bias we had selected a dose of 10 ml and colloid (6% HES) in place of crystalloid. As previous studies showed that colloid has more viscosity, absorbed slowly so may be more effective than crystalloid as EVE for enhancing spinal block.…”
Section: Discussionmentioning
confidence: 99%
“…Daha önce yapılan çalışmalarda da bildirildiği üzere KSEB uygulamasında düşük doz lokal anestezik ajan uygulanarak hızla spinal blok sağlanabilir ve daha sonra epidural ek dozlar ile duyusal blok seviyesi istenilen segmentlere genişletilebilir. [9][10][11][12] KSEB'de düşük doz lokal anestezik ile yeterli blok seviyesine ulaşılması-nın nedeni olarak, epidural aralığa girildiğinde epidural basıncın atmosferik basınca ulaştığını ve dolayısıyla serebrospinal sıvının volüm ve dolaşımını etkileyerek lokal anesteziğin daha iyi yayılımına neden olacağını belirtilmiştir. [13,14] Goy ve ark.…”
Section: Discussionunclassified
“…The literature suggests a strongest effect of epidural volume extension (EVE), in a volume-dependant fashion, in the non-obstetrical population receiving plain bupivacaine [2,3]. In term parturients, factors such as hormone-induced hypersensitivity to neuraxial-administered local anaesthetics, epidural venous plexus engorgement, the baricity of the injected local anaesthetic and the position of the patient may significantly affect the height of the spinal block.…”
Section: A Replymentioning
confidence: 99%